Neonatal rickets in one of identical twins. Issue 10 (October 1982) - Kovar, I Z; Mayne, P; Wallis, J
Abstract : We report a case of rickets in one of identical low birthweight twin infants. Plasma 25-hydroxycholecalciferol concentrations were normal in both infants; there was good clinical response to 1-α hydroxycholecalciferol. We suggest that there was a delay in maturation of renal 25-hydroxycholecalciferol-1α hydroxylase enzyme.